Anal high-risk human papillomavirus infection and high-grade anal intraepithelial neoplasia detected in women and heterosexual men infected with human immunodeficiency virus - Gandra S (Dove Medical Press, 2015)
Sumanth Gandra, Aline Azar, Mireya WessolosskyDivision of Infectious Disease and Immunology, University of Massachusetts Medical School, Worcester, MA, USABackground: Although anal high-risk human papillomavirus (HR-HPV) infection and anal cytological abnormalities are highly prevalent among human immunodeficiency virus (HIV)-infected men who have sex with men (MSM), there are insufficient data on these abnormalities among HIV-infected heterosexual men (HSM) and women. In this study, we evaluated the prevalence of anal HR-HPV, cytological abnormalities, and performance of these screening tests in detecting high-grade anal intraepithelial neoplasia (AIN2+) among our cohort of HIV-infected MSM and non-MSM (HSM and women).Methods: A single-center, retrospective cohort study was conducted with HIV-infected individuals who underwent anal cancer screening with anal cytology and HR-HPV testing from January 2011 to January 31, 2013.Results: Screening of 221 HIV-infected individuals for both HR-HPV and anal cytology showed the presence of HR-HPV in 54% (abnormal anal cytology 48%) of MSM, 28% (abnormal anal cytology 28%) of HSM, and 27% (abnormal anal cytology 34%) of women. Among 117 (53%) individuals with abnormal results (HR-HPV-positive and/or cytology was atypical squamous cells of undetermined significance or above), 67 underwent high resolution anoscopy. Of these 67 individuals, 22 individuals had AIN2+ (17 MSM, four women, and one HSM). HR-HPV correlated better with AIN2+ than with anal cytology on biopsy in both MSM (r=0.29 versus r=0.10; P=0.05 versus P=0.49) and non-MSM (r=0.36 versus r=-0.34; P=0.08 versus P=0.09).Conclusion: Given the presence of AIN2+ in screened HIV-infected HSM and women, routine anal cancer screening in all HIV-infected individuals should be considered. HR-HPV merits further evaluation for anal cancer screening among non-MSM.Keywords: human immunodeficiency virus, anal human papillomavirus, heterosexual men, women, anal cancer